Building Coalitions: Making A Difference Needs Assessments - Thomas M. Archer; Robert Cripe; N.I. McCaslin; Elizabeth B. Bolton; Lisa Guion (EDIS, 2002)
This document is FY501, Part 9 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.